Renin-Angiotensin-Aldosterone System in Women Using Combined Oral Contraceptive: A Systematic Review - Priscilla Araújo dos Santos; Alice Miranda de Oliveira; Caroline Queiroz Alves; Clóvis Figueiredo Souza Filho; Ana Marice Teixeira Ladeia; Jefferson Petto (Federação Brasileira das Sociedades de Ginecologia e Obstetrícia, 2022)
Abstract Objective To describe the effects of combined oral contraceptives (COC) on the renin-angiotensin-aldosterone system (RAAS). Data sourcesThis is a systematic review according to the criteria of Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA), registered in PROSPERO under the ID: CRD42020200019. Searches were performed between August 2020 and December 2021, in the following databases: Medline via Pubmed, Cochrane Central Library, Scientific Electronic Library Online, and Latin American and Caribbean Literature in Health Sciences via Virtual Health Library. The effects of the combined oral contraceptive on plasma renin activity values, plasma renin values, angiotensinogen values- also known as plasma renin substrate- angiotensin, and/or aldosterone values. Study selectionA total of 877 studies were selected and, of these, 10 articles met the eligibility criteria and were included in this review. Data collectionData were combined through qualitative synthesis and included in a spreadsheet previously prepared by the authors. Data synthesisThe collected samples ranged from 18 to 137 participants, totaling 501 women aged between 18 and 49 years throughout all studies. The studies showed increased activity of plasma renin, plasma renin substrate, angiotensin II, and aldosterone in this population. Conclusion The findings of this study suggest that the COC promotes greater activation of the RAAS. Supporting the idea that its use is related to an increased risk of cardiovascular events, including systemic arterial hypertension.